Cophylogeny and specificity between cryptic coral species (Pocillopora spp.) at Mo′orea and their symbionts (Symbiodiniaceae). Issue 20 (29th August 2022) - Johnston, Erika C.; Cunning, Ross; Burgess, Scott C.
Abstract: The congruence between phylogenies of tightly associated groups of organisms (cophylogeny) reflects evolutionary links between ecologically important interactions. However, despite being a classic example of an obligate symbiosis, tests of cophylogeny between scleractinian corals and their photosynthetic algal symbionts have been hampered in the past because both corals and algae contain genetically unresolved and morphologically cryptic species. Here, we studied co‐occurring, cryptic Pocillopora species from Mo′orea, French Polynesia, that differ in their relative abundance across depth. We constructed new phylogenies of the host Pocillopora (using complete mitochondrial genomes, genomic loci, and thousands of single nucleotide polymorphisms) and their Symbiodiniaceae symbionts (using ITS2 and psbA ncr markers) and tested for cophylogeny. The analysis supported the presence of five Pocillopora species on the fore reef at Mo′orea that mostly hosted either Cladocopium latusorum or C. pacificum. Only Pocillopora species hosting C. latusorum also hosted taxa from Symbiodinium and Durusdinium . In general, the Cladocopium phylogeny mirrored the Pocillopora phylogeny. Within Cladocopium species, lineages also differed in their associations with Pocillopora haplotypes, except those showing evidence of nuclear introgression, and with depth in the two most common Pocillopora species. We also found evidence for a new Pocillopora species (haplotype 10), that has so far only been sampled from French Polynesia, that warrants formal identification. The linked phylogenies of these Pocillopora and Cladocopium species and lineages suggest that symbiont speciation is driven by niche diversification in the host, but there is still evidence for symbiont flexibility in some cases.